2020
DOI: 10.1111/wre.12438
|View full text |Cite
|
Sign up to set email alerts
|

Seed retention of ten common weed species at oat harvest reveals the potential for harvest weed seed control

Abstract: We assessed the seed production and shedding pattern of 10 common weed species in two oat fields in Denmark. The aim was to evaluate the possibility of harvesting retained seeds on weeds at crop harvest by a combine harvester based on estimation of weed seed retention. Before flowering, ten plants of each weed species were selected and surrounded by a seed trap comprising of a porous net. When the plants started shedding seeds, the seeds were collected from the traps and counted weekly until oat harvest. Just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Importantly, these studies have identified the opportunity for HWSC to target significant proportions (50-99%) of the seed production of the particularly damaging weeds Palmer amaranth (Amaranthus palmeri), water hemp (Amaranthus tuberculatus), annual ragweed (Ambrosia artemisiifolia L.), Italian ryegrass (Lolium perenne subsp. multiflorum), charlock (Sinapis arvensis) and chickweed (Stellaria media) (Bitarafan and Andreasen 2020;San Martín et al 2021;Schwartz-Lazaro et al 2021a, 2021b.…”
Section: Identifying the Potential Of Hwsc In Global Cropping Systemsmentioning
confidence: 99%
“…Importantly, these studies have identified the opportunity for HWSC to target significant proportions (50-99%) of the seed production of the particularly damaging weeds Palmer amaranth (Amaranthus palmeri), water hemp (Amaranthus tuberculatus), annual ragweed (Ambrosia artemisiifolia L.), Italian ryegrass (Lolium perenne subsp. multiflorum), charlock (Sinapis arvensis) and chickweed (Stellaria media) (Bitarafan and Andreasen 2020;San Martín et al 2021;Schwartz-Lazaro et al 2021a, 2021b.…”
Section: Identifying the Potential Of Hwsc In Global Cropping Systemsmentioning
confidence: 99%
“…Veronica persica Poir., Polygonum aviculare agg. and Anagallis arvensis L. retain up to 60% of their seed at crop maturity, however, weed seed harvest of these species will be poor because of their prostrate growth habit (Bitarafan and Andreasen, 2020c).…”
Section: Prerequisites For the Success Of Hwscmentioning
confidence: 99%
“…A stubble height of around 15 cm is considered as the practical minimum harvest height for most growers in Europe (Bitarafan and Andreasen, 2020c). Problematic grass weed species in Europe such as A. myosuroides, A. spica-venti and L. multiflorum are tall growing (>80 cm) upright plants with erect seed heads, making it possible to capture the retained seeds with the harvester (CABI, 2021a, Akhter et al 2020a, Akgun et al, 2008.…”
Section: Prerequisites For the Success Of Hwscmentioning
confidence: 99%
“…Weed flaming can also effectively control C. bursa-pastoris in the cotyledon stage but requires a higher flaming dose in the rosette stage (2 to 5 leaves) (Sivesind et al 2009). Harvest weed seed control promises to provide a tool for reducing populations of seed banking plants like C. bursa-pastoris; a Danish study identified it as a reasonably good target, i.e., "intermediate," for this control method (Bitarafan and Andreasen 2020).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%